Lower indoor spatial frequency increases the risk of myopia in children - Li, Dan-Lin (2024)
Background/aims: Animal models have shown that the absence of high-frequency visual information can precipitate the onset of myopia, but this relationship remains unclear in humans. This study aims to explore the association between the spatial frequency content of the visual environment and myopia in children. Methods: Images from the rooms of children and their frequently visited outdoor areas were taken by their parents and collected by the researcher through questionnaires. The spatial frequency was quantified using Matlab. Cycloplegic refraction was used to measure the spherical equivalent (SE), and IOL Master was used to measure axial length (AL) and corneal radius (CR). AL/CR ratio was calculated. Results: The study included 566 children with an average age of (8.04±1.47) years, of which 270 were girls (47.7%), and the average SE was (0.70±1.21) D. Image analysis revealed that indoor spatial frequency slope was lower than that of the outdoor environment (-1.43±0.18 vs -1.11±0.23, p<0.001). There were 79 myopic individuals (14.0%). Images from indoor content of myopic children had a lower spatial frequency slope than non-myopic children (-1.47±0.16 vs 1.43±0.18, p=0.03) while there was no significant difference in outdoor spatial frequency slope. Regression analysis indicated that the indoor spatial frequency slope was positively associated with SE value (β=0.60, p=0.02) and inversely related to myopia (OR=0.24, p<0.05). Conclusion: The spatial frequency of the outdoor environment is significantly higher than that of the indoor environment. Indoor spatial frequency is related to children's refractive status, with lower indoor spatial frequency being associated with a higher degree of myopia.